2021
DOI: 10.1038/s41598-021-82772-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating very high energy electron RBE from nanodosimetric pBR322 plasmid DNA damage

Abstract: This paper presents the first plasmid DNA irradiations carried out with Very High Energy Electrons (VHEE) over 100–200 MeV at the CLEAR user facility at CERN to determine the Relative Biological Effectiveness (RBE) of VHEE. DNA damage yields were measured in dry and aqueous environments to determine that ~ 99% of total DNA breaks were caused by indirect effects, consistent with other published measurements for protons and photons. Double-Strand Break (DSB) yield was used as the biological endpoint for RBE calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
1
30
2
Order By: Relevance
“…This conclusion was further illustrated by the fact that the cell survival curves for the VHEE beams were indistinguishable to those of the clinical beams, thus resulting in a theoretical RBE of ~ 1 for all electron energies. This result is in accordance with the first experimental evaluation of VHEE RBE published recently by Small et al 28 which was found to be close to 1, although plasmid DNA damage was used as the biological endpoint for the RBE calculation instead of cell survival. Both results give confidence to the clinical implementation of VHEE radiotherapy, as the biological damage caused by VHEEs are expected to be similar to those caused by conventional radiotherapy modalities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion was further illustrated by the fact that the cell survival curves for the VHEE beams were indistinguishable to those of the clinical beams, thus resulting in a theoretical RBE of ~ 1 for all electron energies. This result is in accordance with the first experimental evaluation of VHEE RBE published recently by Small et al 28 which was found to be close to 1, although plasmid DNA damage was used as the biological endpoint for the RBE calculation instead of cell survival. Both results give confidence to the clinical implementation of VHEE radiotherapy, as the biological damage caused by VHEEs are expected to be similar to those caused by conventional radiotherapy modalities.…”
Section: Discussionsupporting
confidence: 91%
“…This is mainly due to a lack of dedicated research platforms. Very recently, Small et al 28 performed the first plasmid DNA irradiations carried out with VHEEs at the CLEAR user facility at CERN, to determine their efficacy to produce DNA damage. VHEE RBE evaluated in terms of double strand break yield was found to be close to 1 for dry plasmids and 1.1–1.2 for wet plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…Two irradiation areas are available for users to study X-band RF components (typically around 12 GHz) and novel concepts such as the use of plasma or THz-wavelength radiation for charged-particle acceleration, but also the radiation hardness resistance of electronic devices and medical applications. Several studies on the use of VHEE beams for clinical employment were already conducted at CLEAR, especially in the field of dosimetry in very high dose rates conditions [ 51 , 52 , 71 , 87 , 88 ].…”
Section: Accelerators For Vheesmentioning
confidence: 99%
“…No difference in the calculated RBE was found compared to conventional 20 MeV electron beams, although the doseaveraged linear energy transfers (LET d ) for VHEEs were estimated to be slightly higher (0.4-0.8 keV/µm) than those of the low-energy electrons (0.255 keV/µm). In another recent study [71], the first plasmid irradiation experiments were performed using VHEEs between 100 and 200 MeV at the CLEAR facility, showing little variation in double strand-break (DSB) induction with beam energy, and no statistically different variation in DSB yield between conventional or ultra-high dose rates. In that study, Geant4-DNA MC simulations were also carried out and showed that theoretical RBE (evaluated at 0.22 keV/µm for VHEE beams), physical damage to DNA, and RBE DSB calculations were similar between VHEEs, conventional 60 Co X-rays, and low-energy electrons.…”
Section: Biological Specificities Of High-energy Electronsmentioning
confidence: 99%
“…To this end, pBR322 plasmid DNA (Thermo Fisher Scientific, Inc.) was selected for its lack of higher-level biological processes that might otherwise confound the 𝑅𝐵𝐸 𝐷𝑆𝐵 of FDR versus SDR irradiation. This reductionist DNA approach has been used in other radiotherapy DNA damage studies, [30][31][32][33] and lends itself naturally to study whether differences observed between FDR and SDR irradiation can be understood at least partially in terms of fundamental radiochemical mechanisms or whether they are attributed solely to higher level biochemical cellular pathways and/or biological system responses. To test this, we constructed DNA-based phantoms comprising plasmid DNA and exposed them to FDR and SDR irradiation to quantify the resulting yields of SSBs and DSBs.…”
Section: Introductionmentioning
confidence: 99%